What is to be done about violence against women?: gendered violence(s) in the twenty-first century - Fitz-Gibbon, Kate (Routledge, Taylor & Francis Group, 2024)
"This book maps the problems and possibilities of the policies and practices designed to tackle violence against women in the domestic sphere over the last 40 years. In 2018, the United Nations declared the home the most dangerous place for women around the word, and in early April 2020, the United Nations Population Fund predicted that for every three months that government enforced lockdowns in response to coronavirus an additional 15 million cases of domestic violence would occur worldwide. This book asks the simple yet critical question: how can governments best ensure women's safety in the twenty-first century? Taking its title from Elizabeth Wilson's 1983 book and her three-level approach of considering the role of social policy, the law and ideology, Fitz-Gibbon and Walklate draw on their expertise on femicide, domestic abuse and family violence to examine the salience of global and local policy and practice responses to such violence(s), and to ask timely questions about the ongoing value of the recourse to the criminal law for twenty-first century policy. Comparative in orientation, appreciative of the importance of geographical and social context, and committed to understanding the historical processes that continue to frame policy responses, this book takes a long hard look at what has and has not been achieved in relation to domestic abuse and family violence and seeks to challenge all that has come to be taken for granted in responding to such violence(s). Published in the 40th Anniversary of Elizabeth Wilson's ground-breaking contribution, this book is destined to become a classic in its own right. It is essential reading for all those engaged in feminist criminology, gender and crime, family and domestic violence, and violence against women"--